The effect of the standardized fartlek training method in developing transitional speed and some basic skills for indoor soccer players (Damu Journal of Sport Sciences, 2024)
The research aims to prepare exercises using the standardized fartlek method to develop transitional speed and some basic skills for indoor soccer players, and to identify the effect of exercises specific to the standardized fartlek method to develop transitional speed and some basic skills for individuals in the research sample.(To achieve the goal, the researcher used the experimental method with a pre- and post-test to suit it) with the research problem, and the research community consisted of players from Baghdad clubs participating in the Iraqi Premier League in indoor football for the season (2023-2024), which numbered (6) clubs. The sample was chosen intentionally, and they are the players of the (Science and Technology) Club, numbering (20) players. (12) players were chosen to represent the main experimental sample after randomly excluding (4) players as a survey sample, as well as excluding goalkeepers, numbering (3), and thus the sample will represent (18.18%) of the research community. (The researcher conducted the pre- and post-test for the research sample members, and appropriate statistical treatments were conducted). The researcher concluded that "the exercises specific to the standardized fartlek method led to the development of speed endurance and transitional speed", and that the development of transitional speed had an impact on the development of some basic skills in indoor football, and that the variety of exercises and the way they were produced had a good psychological reality among the sample members. Which increased the enthusiasm of the players and raised their morale when performing the exercises.